The female red jungle fowl (Gallus gallus gallus) reproductive investment stimulated by male attractiveness - ASMORO LELONO; BERND RIEDSTRA; TON GROOTHUIS (Society for Indonesian Biodiversity, 2024)
Abstract. Lelono A, Riedstra B, Groothuis T. 2024. The female red jungle fowl (Gallus gallus gallus) reproductive investment stimulated by male attractiveness. Biodiversitas 25: 2931-2936. To maximize their capacity for reproduction, mothers are expected to modify their investment in offspring based on the quality of their mates. A recent study showed that females in female-care only species do so by investing more in egg mass when mated with attractive males rather than in other reproductive traits. In our study, we investigated how red jungle fowl (Gallus gallus gallus) mothers invest in clutch production based on the size of the male's comb, a trait signaling attractiveness. We randomly paired 14 females with 14 males of either large or small combs and monitored their egg laying, clutch completion, and brood rearing. Following the initial clutch, we exchanged male partners and permitted females to establish up second generation. We found that females who were partnered with males who had bigger combs laid down their eggs earlier after pairing compared to those paired with males with smaller combs. However, there were no variations in egg mass or clutch size that we could find. Furthermore, the size of the male's comb influenced the growth and body condition of female chicks, with those sired by males with larger combs being heavier and in better condition at twenty-four weeks old. These data support the premise of the positive Differential Allocation (DA) hypothesis, where maternal investment varies with mate quality, rather than the negative DA, where females more investment in offspring from lower quality mates.